Pengaruh Kepercayaan Merek, Citra Merek, dan Kepuasan Merek Terhadap Loyalitas Merek Serta Keinginan Pembelian Ulang Koran Jawa Pos Pada Masyarakat Surabaya - Hendri Rahman Susetyo; Mochamad Rizal Yulianto (Jurnal Manajemen dan Bisnis Indonesia, 2017)
The purpose of this study is to examine the influence of brand trust, brand image, and brand satisfaction on brand loyalty as well as the desire to repurchase Jawa Pos newspaper in Surabaya city. Based on the literature review, this research hypothesis states that brand trust, brand image, and brand satisfaction have an effect on brand loyalty, besides the result of literature review indicate that brand loyalty influence to repurchase desire. The data of this study were collected by using questionnaires from respondents consisting of 210 Jawa Pos newspaper customers in Surabaya. Hypothesis testing technique is done by using structure equation model analysis (sem) with SmartPLS statistic application. The results of this study indicate that brand trust, brand image, and brand satisfaction have a positive effect on brand loyalty, as well as brand loyalty have a positive effect on repurchase desire. Specifically, this study shows that loyal customers will continue to make repeat purchases. Keywords: Image, trust, satisfaction, loyalty, brand, repurchase intentions.